Uses of plants as medicine by Muna People, Sub District Wakarumba, District Muna, Province of SoutheastSulawesi - FLORENTINA INDAH WINDADRI; MULYATI RAHAYU; TAHAN UJI; HIMMAH RUSTIAMI (Society for Indonesian Biodiversity, 2006)
North Wakarumba is one of subdistrict lies in the north of Buton Island, close to North Buton Nature Reserve. More than one etnic live in this sub district such as Muna as the biggest ethnic. Muna people have unique behavior in the plant using and environment management including protecting forest and its surrounding area. Study on the plant usage as traditional medicinal plant has been done by interviewing local people. The result of the research was got 61 species of medicinal plants, where 6 species of them have never been published at the Index of Indonesian Medicinal Plants. Thirty-eight plants species could be found wildly and 16 of them occur in North Buton Nature Reserve areas. Bark of 10 species reported as after giving birth medicine. Grinding of Epipremnum pinnatum leaves could be used as wound medicine. Leaf of Terminalia catappa could be used as anti diarrhea.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: North Wakarumba, Muna ethnics, medicinal plant, Buton